THE NOVEL "THE BRAVE ADVENTURES OF LAPITCH" AS A BASIS FOR PROJECT TEACHING AT A TEACHER TRAINING COLLEGE - Vesna M. Grahovac-Pražić; Ana V. Vivoda; Sanja G. Vrcić-Mataija (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2014)
<!-- p { margin-bottom: 0.1in; line-height: 120%; } --> In order to introduce future teachers to project teaching and raise awareness of its correlation with teaching practices, as well as link linguistic communication with artistic areas in accordance with NCC, the project "Let's play Lapitch" was designed within the celebration of the centennial of the novel "The Brave Adventures of Lapitch" by Ivana Brlić Mažuranić. Students became acquainted with the literary-theoretical characteristics of the novel and independently performed a transformation of the narrative into the illustrated form. An intimate visual communication of the students with the literary text was based on the hard book cover, introducing them to the artistic discipline of bookbinding. The creative process included an interpretation of the literary text within the fi eld of a new medium - the artistic book required visual and narrative coherence, which created a strong link between the courses Children's literature and Extracurricular art activities. The goal of the project was methodically designed to bring together the teachers, the students and the pupils with the aim of analyzing the reception of the novel and expanding their experience. The project intertwined different areas of studying the mother tongue (language, literature, language expression), but it also included a practical realization in the classroom, which is the main point of teacher education. Finally, the project was concluded by a joint public presentation of the works made by the students and the elementary school pupils at the Museum of Lika in Gospić, which enabled the evaluation of the project. Project "Let's play Lapitch" confi rmed the independent research of the students and the pupils, the exchange of ideas and collaborative forms of work, and also encouraged cooperation between educational institutions in the city.